The Dress Code for Lawyers: In Search of Change with Climatic Compatibility in Bangladesh (Global Journal of Human-Social Science, 2012)
Dress code is a part of dignity and professionalism with little exception. The outfit of Judges and Advocates with judicial robes seems a mark of dignity and loyalty towards court and justice. Americans refused to adopt the judicial attire of the British after independence. Almost all countries in the Indian subcontinent are in debt to the British for the development of their jurisprudence including dress code. Even, the British has relaxed wearing judicial costumes but these countries including Bangladesh have slight headache to suit the dress code for lawyers as per climatic conformity and culture even after the departure of the British. India has modified dress code for lawyers to a tiny extent but the practice is still like colonized India reminding silent domination of the British. This write up is a venture to explore the historical chronicles of the judicial attire across the world and theirs recent changing trends and practices with a view to seek a meaningful transformation in Bangladesh.
Keywords: lawyers; dress code; bangladesh; climatic compatibility; adjustment; change